A Case of Refractory Atrial Fibrillation Treated with Amiodarone - Alam, Md Zahid; Karmaker, Pranob; Ara, Rowsan; Quader, Monzoor; Khan, MM Zahurul Alam; Hoque, Shabnam Jahan (Bangladesh Journal of Medicine, 2013)
We report a case of atrial fibrillation (AF) of unknown duration with fast ventricular rate which was refractory to intravenous (i.v.) digoxin, verapamil and DC (direct current) shock regarding rate control. Amiodarone was given in bolus & then in maintenance dose which ultimately controlled the rate and finally converted into sinus rhythm. DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13622 Bangladesh J Medicine 2010; 21: 108-110